(E)-α, β-unsaturated amides from tertiary amines, olefins and CO via Pd/Cu-catalyzed aerobic oxidative N-dealkylation. Issue 15 (22nd January 2015) - Shi, Renyi; Zhang, Hua; Lu, Lijun; Gan, Pei; Sha, Yuchen; Zhang, Heng; Liu, Qiang; Beller, Matthias; Lei, Aiwen
Abstract : A novel Pd/Cu-catalyzed chemoselective aerobic oxidative N -dealkylation/carbonylation reaction has been developed for the efficient and straightforward construction of synthetically useful and bioactive ( E )-α, β-unsaturated amide derivatives. Abstract : A novel Pd/Cu-catalyzed chemoselective aerobic oxidative N -dealkylation/carbonylation reaction has been developed. Tertiary amines are utilized as a "reservoir" of "active" secondary amines in this transformation, which inhibits the formation of undesired by-products and the deactivation of the catalysts. This protocol allows for an efficient and straightforward construction of synthetically useful and bioactive ( E )-α, β-unsaturated amide derivatives from easily available tertiary amines, olefins and CO.